Influent and effluent greywater quality in a long-term evaluation of a constructed wetland in Norway - Sami, Mashreki; Hedström, Annelie; Kvarnström, Elisabeth; Herrmann, Inga (Luleå University of Technology, 2026)
The dataset presented here consists of raw data on the quality of influent greywater generated from residential buildings (100 PE) and the effluent quality of greywater after treatment using a constructed wetland that was built in 2001. A total of 15 samples of influent and effluent samples were taken between February 2023 and Jan 2024, in different months to assess seasonal variations. This 2023-2024 data was compared with the few existing effluent quality data from 2001-2014. The analyzed parameters include organic matter (e.g. TSS, BOD, COD, TOC), total nitrogen, total phosphorus, salt, and microorganisms (E. coli, enterococci, Clostridium perfringens, Legionella spp, Pseudomonas aeruginosa, and Campylobacter). Supporting parameters e.g. turbidity, pH, and conductivity are also included in the dataset.

Files
1. Study_Description: This file includes the summary of the research study, data collection and the standard analytical methods used for analyzing different parameters.
2. Greywater_quality: The influent and effluent concentrations of all parameters analyzed during all sampling events including the previous effluent data from 2001-2014.

Datasetet som presenteras här består av rådata för kvalitet på inkommande bad-, disk- och tvätt-vatten (BDT-vatten) från en bostadshus (100 PE) och kvaliteten på det behandlade gråvattnet efter rening i en bevuxen filterbädd, som byggdes år 2001. Totalt togs 15 prover av både inkommande och utgående vatten mellan februari 2023 och januari 2024, under olika månader för att utvärdera säsongsvariationer. Dessa data från 2023–2024 jämfördes med befintliga data för utgående vatten från 2001–2014. De analyserade parametrarna inkluderar organiskt material (t.ex. TSS, BOD, COD, TOC), totalkväve, totalfosfor, salter och mikroorganismer (E. coli, enterokocker, Clostridium perfringens, Legionella spp., Pseudomonas aeruginosa och Campylobacter). Stödparametrar såsom turbiditet, pH och konduktivitet ingår också i datasetet.

Files
1. Study_Description: This file includes the summary of the research study, data collection and the standard analytical methods used for analyzing different parameters.
2. Greywater_quality: The influent and effluent concentrations of all parameters analyzed during all sampling events including the previous effluent data from 2001-2014.
Kvalitet på inkommande och utgående BDT-vatten under 23 års tid från en konstruerad, bevuxen filterbädd i Norge
Keywords: ORGANIC MATTER; water quality; vattenkvalitet; phosphorus; fosfor; nitrogen; kväve; pathogens; patogener; greywater; gråvatten; wetlands; våtmarker; constructed wetlands; Environmental Engineering; Naturresursteknik; Environmental Management; Miljöteknik och miljöledning; Water Treatment; Vattenbehandlingsbioteknik